Efektivitas Teknik Mindfulness Metode STOP dalam Menurunkan Gejala Risiko Perilaku Kekerasan: Analisis Berdasarkan Etiologi - Gabriela Rosario Asriviananda; Yunita Astriani Hardayati (Lontara Journal of Health Science and Technology, 2026)
Risk for Other-Directed Violence (RODV) is a critical issue in psychiatric nursing that requires rapid emotional regulation. The STOP mindfulness technique (Stop, Take a breath, Observe, Proceed) is a cognitive approach to enhancing patients' self-awareness in managing anger. However, its effectiveness may vary depending on the etiology of RODV. To describe the application of the STOP mindfulness technique in reducing signs and symptoms in RODV patients. This case report design involving four RODV patients. Subjects were categorized into two groups: the Core Problem group  and the Effect group due to hallucinations. The intervention consisted of six sessions, including three 20-minute STOP training sessions. Evaluation instruments included RODV sign and symptom observation sheets administered before and after the intervention. The core problem group showed a significant reduction in symptoms with 3 points. Conversely, the effect group showed less significant improvement with 2-3 points. The STOP mindfulness technique is highly effective for RODV patients without sensory perception disorders. In RODV patients driven by hallucinations, the intensity of hallucinations acts as a primary barrier to achieving mindfulness. Nurses are advised to stabilize hallucinatory symptoms prior to administering STOP cognitive interventions for optimal outcomes.